Pregnancy with severe preeclampsia, acute kidney injury and nephrotic syndrome - Serudji, Joserizal; Yuad, Haviz; Ambelina, Syntia (Fakultas Kedokteran Universitas Andalas, 2023)
Background: Preeclampsia is one of the main causes of maternal death every year. Preeclampsia can have badconsequences for both the mother and the fetus. Complications in the mother in the form of HELLP syndrome(Hemolysis, Elevated Liver Enzyme, Low Platelet), pulmonary edema, kidney disorders, bleeding, placentalabruption and even maternal death. Complications in infants can be premature birth, fetal distress, low birthweight or intra uterine fetal death (IUFD).Case Report: A 34 year old female patient was brought to the emergency room of Dr. M. Djamil Padang, sent tothe Batusangkar Private Hospital with complaints of shortness of breath which has been increasing when lyingdown. Physical examination found blood pressure 190/136. The patient was diagnosed with G2P1A0H1 gravidpreterm 25-26 weeks, PEB on maintenance dose MgSO4 regimen from outside, suspected nephrotic syndrome,CAP with hypoxemia, pleural effusion, AKI with metabolic acidosis, UTI, hyponatremia, hypoalbuminemia.Discussion: Preeclampsia, eclampsia and HELLP syndrome are serious and life-threatening conditions faced bypregnant women. Early diagnosis and prompt treatment via a multidisciplinary team in the ICU setting canprevent complications and reduce morbidity and mortality. The most common indications for intubation andmechanical ventilation are respiratory failure and hemodynamic instability. The cause of death in this patientwas multiple organ failure which was exacerbated by suspected nephrotic syndrome and suspected SLE.